2018
DOI: 10.7759/cureus.3602
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Right Vertebral Artery from the Right Common Carotid Artery

Abstract: The anomalous origin of the right vertebral artery (VA) from the right common carotid artery (CCA) is a rare vascular anomaly, which is usually clinically asymptomatic and found incidentally during angiographic examinations. This anomaly is invariably associated with an aberrant right subclavian artery (RSCA). Approximately 31 cases have been reported in the literature. We present a case of a right VA originating from the right CCA in a patient with Down syndrome and discuss the imaging findings, embryological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Embryologically, the development of the vertebral artery is contributed by the cervical intersegmental arteries, which normally originate from the subclavian artery [5]. Initially, these arteries are the major source of blood supply to the cervical nerves and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Embryologically, the development of the vertebral artery is contributed by the cervical intersegmental arteries, which normally originate from the subclavian artery [5]. Initially, these arteries are the major source of blood supply to the cervical nerves and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have reported abnormal VAs with different genesis including trunk of thyrocervical artery, brachiocephalic artery, common carotid artery, and the aorta [9][10][11][12]. However, there are less than 5 studies which reported that VA originates from external carotid artery [8,[13][14][15]. Elevated risk for cerebrovascular accidents including ath-for cerebrovascular accidents including ath-for cerebrovascular accidents including atherosclerosis, intracranial vascular deformities, arterial cutting up and resulting intracranial complexities due to confusion of the blood flow proceeding from aberrant origin of the VAs have been illustrated in many studies [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are less than 5 studies which reported that VA originates from external carotid artery [8,[13][14][15]. Elevated risk for cerebrovascular accidents including ath-for cerebrovascular accidents including ath-for cerebrovascular accidents including atherosclerosis, intracranial vascular deformities, arterial cutting up and resulting intracranial complexities due to confusion of the blood flow proceeding from aberrant origin of the VAs have been illustrated in many studies [8][9][10][11][12][13][14][15][16]. The extra-cranial section of the VA is often affected by atherosclerosis leading to a restriction notably in its root [17].…”
Section: Discussionmentioning
confidence: 99%
“…23 If it occurs in the lower – third to sixth – intersegmental arteries, the result is an abnormal origin of the vertebral artery from the aortic arch or the common carotid artery, with the latter being the most common RVA anomaly. 19,23…”
Section: Aortic Arch Variants and Anomaliesmentioning
confidence: 99%